Therapeutic Potential of SphK1 Inhibitors Based on Abnormal Expression of SphK1 in Inflammatory Immune Related-Diseases - Bu, Yanhong; Wu, Hong; Deng, Ran; Wang, Yan (Frontiers in Pharmacology, 2021)
Sphingosine kinase 1(SphK1) a key enzyme that catalyzes the conversion of sphingosine (Sph) to sphingosine 1-phosphate (S1P), so as to maintain the dynamic balance of sphingolipid-rheostat in cells and participate in cell growth and death, proliferation and migration, vasoconstriction and remodeling, inflammation and metabolism. The normal expression of SphK1 maintains the balance of physiological and pathological states, which is reflected in the regulation of inflammatory factor secretion, immune response in traditional immune cells and non-traditional immune cells, and complex signal transduction. However, abnormal SphK1 expression and activity are found in various inflammatory and immune related-diseases, such as hypertension, atherosclerosis, Alzheimer's disease, inflammatory bowel disease and rheumatoid arthritis. In view of the therapeutic potential of regulating SphK1 and its signal, the current research is aimed at SphK1 inhibitors, such as SphK1 selective inhibitors and dual SphK1/2 inhibitor, and other compounds with inhibitory potency. This review explores the regulatory role of over-expressed SphK1 in inflammatory and immune related-diseases, and investigate the latest progress of SphK1 inhibitors and the improvement of disease or pathological state.